การดูดซับสารตะกั่วในน้ำด้วยซิลิกาที่มีรูพรุนขนาดกลางที่เจือด้วยซีลีเนียม - ชารฎา สมคิด (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
In this study, new mesoporous silica adsorbent materials for lead adsorption were prepared by doping selenium into SBA-15 (Se-doped SBA-15). The synthesis methods were divided into two routes: For the first one, selenium powder was used as a reactant, and the weight ratios of silica to selenium were varied as 1:0.1, 1:0.2 and 1:0.3. In the second route, sodium selenite was used as a reactant with weight ratio of Si:Se = 1:0.3 with 7 days of crystallization. Then, the products were synthesized by hydrothermal method at 100 °C. XRD, FESEM, SEM/EDS, TEM, XRF, FTIR and Surface Area Analyzer techniques were used to characterize the prepared products. To study on the adsorption of lead by Se-doped SBA-15, AAS was used to quantify lead concentration. Furthermore, the effects of initial concentration of lead, pH and shaking time for lead adsorption were investigated. The results indicated that the adsorption was the experiment with two hours shaking time at pH 5, resulting in the highest percent removal of 24.40.